Comparative Study on Hepatoprotective Effects of Alcohol Extract and Total Flavonoids of Penthorum chinense Pursh against Alcohol-induced Subacute Liver Injury in Mice - Hong JIU; Manling FU; Hongsheng LIU; Shibo ZHANG; Xiaofang HOU; Jiqiang YAO; Yefei YUAN (Shipin gongye ke-ji, 2023)
Object: To compare the hepatoprotective effects of alcohol extract and total flavonoids of Penthorum chinense Pursh on alcohol-induced subacute liver injury in mice. Methods: The mice were randomized into the normal group, model group, positive group (bifendate, 150 mg/kg), ethanol extract of Penthorum chinense Pursh with three different dose treatment groups (400, 800 and 1600 mg/kg), and total flavonoids of Penthorum chinense Pursh with three different dose treatment groups (100, 200 and 400 mg/kg). The model of subacute alcoholic liver injury in mouse was set up by intragastric administration of alcohol. The liver index, pathological changes of liver tissue and serum biochemical indexes were measured in each group. Results: Compared with mice in the model group, the hepatic index was decreased significantly (P<0.05), the liver injury pathological state was ameliorated, the activities of serum alanine transaminase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALP), lactic dehydrogenase (LDH) and the content of total bilirubin (TBIL), total cholesterol (TC), triglycerides (TG), low density lipoprotein cholesterol (LDL-C) were decreased significantly (P<0.05, P<0.01) in the high and medium treatment groups of alcohol extract and total flavonoids of Penthorum chinense Pursh. The activities of serum ALT, AST, ALP, LDH as well as the content of TBIL, TC, TG and LDL-C in the total flavonoids group were significantly lower than those in the alcohol extract group with the same crude drug dose (P<0.05, P<0.01). Conclusion: Both alcohol extract and total flavonoids of Penthorum chinense Pursh can protect subacute alcoholic liver injury, but total flavonoids does better than alcohol extract. The total flavonoids is a main functional component of Penthorum chinese Pursh to protect alcoholic liver injury.